Enhanced biogas separation performance of nanocomposite polyethersulfone membranes using carbon nanotubes - Tutuk Djoko Kusworo; Budiyono Budiyono (Waste Technology, 2013)
This study is performed primarily to investigate the effect of chemical modification on carbon nanotubes surface towards biogas purification performance of mixed matrix membrane. In this study, polyethersulfone (PES)-carbon nanotubes mixed matrix hollow fiber membrane for modified and unmodified carbon nanotubese were spun using dry/wet spinning technique. The modified carbon nanotubes were prepared by treating the carbon nanotubes with acid treatment to allow PES chains to be attached on carbon nanotubes surface. The results from the FESEM, DSC and FTIR analysis confirmed that chemical modification on carbon nanotubes surface had taken place. Meanwhile, the nanogaps in the interface of polymer and carbon nanotubes were appeared in the PES mixed matrix membrane with unmodified of carbon nanotubes. The modified carbon nanotubes mixed matrix membrane increases the mechanical properties, the productivity and purity of biogas compare to neat PES and unmodified carbon nanotubes mixed matrix membrane. For PES-modified carbon nanotubes mixed matrix membrane the maximum selectivity achieved for CO2/CH4 is 32.59.